The Design of User Interface and User Experience in Rodanya Masbagia's Information System: using Design Thinking Methodology - Maulana, Ibal Afib; Primadewi , Ardhin; Hanafi , Mukhtar; Orbawati, Eny Boedi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Magelang City has become an administrative city and MSMEs (Micro, Small, and Medium Enterprises) as the backbone of the economy in the city. In several regions MSMEs are utilizing digital technology, which has great potential for large-scale sales. The Government of Magelang City has implemented a community empowerment system called the Program for Empowering Community that Advanced, Healthy, and Happy Society (Rodanya Masbagia). This program aims to enhance the empowerment of the community through the local government's budget (APBD) provided by the Magelang City Development Planning Agency (Bappeda). The main challenge faced by MSMEs entrepreneurs is the limitation in selling their products widely, resulting in low demand for their merchandise. There is a sales platform for MSMEs in Rodanya Masbagia’s system especially terms of product marketing. It has a feature implemented where we are not able to reach a wide market. Therefore, there is a need to develop additional features to facilitate widespread product sales. This system is created and designed using the Design Thinking Methodology, which consists of several stages: empathize, define, ideate, prototype, and test. The results of this study underwent testing using the Maze platform to facilitate the system's trial. There were 25 respondents involved in testing the prototype in Figma. The average success rate of the testing was 80% based on predefined metrics. Task 1 achieved a success rate of 90%, task 2 had a success rate of 75%, task 3 had a success rate of 80%, task 4 achieved a success rate of 100%, and task 5 had a success rate of 80%. During the testing phase, users were able to complete the tasks, but some tasks posed difficulties. The results of this study with an average of satisfied user feedback (85%) related to the recommended UI/UX design. It can be concluded that there is a need to improve the performance of the design to prevent users from feeling confused or encountering difficulties when using the product.